Trans-Border Crimes and Nigeria’s National Security - Momoh, Salifu Achile (Kashere Journal of Politics and International Relations, 2024)
Over the years, Nigeria has become a hub for trans-border criminal activities such as; banditry, drugs and human trafficking, oil bunkering, small arms and light weapons smuggling, armed robbery and kidnappings, money laundering etc, which in turn constitutes a threat to national security. These threats do not only endanger the lives and properties of Nigerian citizens but also, the survivability and development of the country with negative impact on the rule of law, economic activities and growth, human rights and general societal advancement. This study set out to examine trans-border crimes in Nigeria and its implication on national security. The study relied extensively on secondary sources of data. The secondary data were sourced from textbooks, Journals, magazines, periodicals and internet, reports etc. The collected data were analyzed qualitatively in order to arrive at a synthesis and make valuable deductions. The study revealed that; the causes of trans-border crimes are traced to factors which includes; poverty, unemployment, decline in social values and other societal issues. From the foregoing, some recommendations were proffered which includes; the need for the Nigerian government as a matter of urgency to address the issue of trans-border crimes in a holistic and coordinated manner, invest in capability to trace, detects, and freeze or confiscate criminal proceeds or assets, creation of employment opportunities to alleviate poverty, strengthen international cooperation in the fight against trans-border crimes as well as training and re-training of security personnel on the modern trends in migration and border management.